(untitled) (Journal of the Society for Musicology in Ireland, 2021)
With the publication in 1762 of Fingal, the ancient epic poem James Macpherson claimed to have reconstructed from Erse sources, scholarly warfare broke out. The hitherto unassailable Irish bard Oisín was unexpectedly confronted with a rival Scottish claimant to the authorship of the Fionn Mac Cumhaill saga: Ossian. A consensus quickly emerged among outraged Irish antiquarians that Macpherson was a very clever fraudster who had ‘usurped the Fenian cycles of Gaelic Ireland’ for commercial gain. The controversy refused to die down, and half a century later there was still no final verdict on the alleged hoax. This article provides fresh perspectives on this controversy.